The Conflict of Private-National Interests in the Divestation of PT. Newmont Nusa Tenggara’s Shares (The Study on Newmont Divestation 2008-2016) - Ferdi Hasiman; Julian aldrian Pasha (Universitas Tidar, 2018)
The 1945 Constitution mandates that strategic mining must be controlled by the state. Not by foreign corporations. Based on that mandate, Indonesian government is struggling for the shares divestment of Newmont Nusa Tenggara (NNT), an American based mining company. NNT operates the Batu Hijau and the Elang Dodo Rinti mine. NNT’s Contract of Work mandates NNT to divest shares of 51 percent. NNT disobeyed the divestment order. In the divestment process, there is a conflict of private-national interests. The divestment process becomes an event to seize the oligarchy. In some term, a new oligarchy regulates Newmont